2021
DOI: 10.1186/s12887-021-02881-z
|View full text |Cite
|
Sign up to set email alerts
|

Can high-flow nasal cannula reduce the risk of bronchopulmonary dysplasia compared with CPAP in preterm infants? A systematic review and meta-analysis

Abstract: Background Bronchopulmonary dysplasia (BPD) is a chronic lung disease that affects the premature lung, and to reduce its incidence has been used non-invasive ventilatory support, such as continuous positive airway (CPAP) and high-flow nasal cannula (HFNC). Thus, the objective of this review was to assess whether the use of high flow nasal cannula (HFNC) compared to continuous positive airway pressure (CPAP) decreases the risk of bronchopulmonary dysplasia (BPD) in premature newborns. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
(99 reference statements)
1
9
0
Order By: Relevance
“…The complications of NCPAP are similar to those of HFNC; it has been reported that the incidence of nasal trauma with NCPAP is higher than that with HFNC 18,22 . Conversely, some reports have shown that the incidence does not differ between the two modes 23,24 . This may be due to the different possible methods to care for infants with NCPAP or HFNC in each institute.…”
Section: Modes Of Noninvasive Respiratory Support and Their Character...mentioning
confidence: 99%
See 1 more Smart Citation
“…The complications of NCPAP are similar to those of HFNC; it has been reported that the incidence of nasal trauma with NCPAP is higher than that with HFNC 18,22 . Conversely, some reports have shown that the incidence does not differ between the two modes 23,24 . This may be due to the different possible methods to care for infants with NCPAP or HFNC in each institute.…”
Section: Modes Of Noninvasive Respiratory Support and Their Character...mentioning
confidence: 99%
“…18,22 Conversely, some reports have shown that the incidence does not differ between the two modes. 23,24 This may be due to the different possible methods to care for infants with NCPAP or HFNC in each institute. Feeding intolerance may also occur due to intestinal distension, called CPAP belly syndrome.…”
Section: Nasal Continuous Positive Airway Pressurementioning
confidence: 99%
“…87 They found no difference for BPD rate (RR = 1.10, 95% CI = 0.90-1.34), 87 however, the quality of evidence was very low. 87 After the acute and most critical phase of respiratory disease, nHFT is often preferred by caregivers and family for simple usability and enhanced patients comfort. [88][89][90] Meta-analysis comparing nHFT with different noninvasive respiratory support modes in infants <37 weeks showed that nHFT is the most effective support mode for preventing nasal injury 84,85,91 nHFT compared to binasal prong CPAP reduce the risk of nasal injury with a risk difference −0.14, 95% CI = −0.17 to −0.10 (seven studies of 1570 neonates).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Identified risk factors for treatment failure were GA < 30 weeks and a fraction of inspired oxygen at start respiratory support >0.30 86 . A recent systematic review and meta‐analysis comparing nHFT and nCPAP looked at BPD as primary outcome in infants <37 weeks regardless of the timing of treatment initiation (13 RCTs, 2038 neonates) 87 . They found no difference for BPD rate (RR = 1.10, 95% CI = 0.90–1.34), 87 however, the quality of evidence was very low 87 .…”
Section: Noninvasive Respiratory Support In the Nicusmentioning
confidence: 99%
See 1 more Smart Citation